Quality Of Service, Tax Understanding, And Tax Sanctions, Effect On Personal Taxpayer Compliance - Maulidatul Chasanah; Syaiful Syaiful (INNOVATION RESEARCH JOURNAL, 2022)
The background in this study is that there is a phenomenon that the realization of state revenues from the tax sector has the largest contribution, which each year experiences ups and downs compared to non-tax revenues. This study aims to test Service Quality, Tax Understanding, and Tax Sanctions, Influence on Individual Taxpayer Compliance. This research uses quantitative methods. The population in this study amounted to 57, while the sampling used the Non Probability Sampling technique using saturated sampling. The reason is because the population size is relatively small. The sample studied by the researcher is 57 taxpayers. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For the test tool, the Statistical Package for the Social Sciences (SPSS) is used. The results of this study indicate that the quality of tax services has a positive and significant effect on taxpayer compliance, tax understanding has a positive and significant effect on taxpayer compliance, and tax sanctions have a positive and significant effect on taxpayer compliance.